BRD7 restrains TNF-α-induced proliferation and migration of airway smooth muscle cells by inhibiting notch signaling. (12th September 2022) - Li, Hong; Yang, Tian; Chen, Tianjun; Liu, Ya; Pang, Yamei; Yang, Lan
Abstract: Objective : Bromodomain-containing protein 7 (BRD7) is a key component of the switch/sucrose non-fermentable complex that participates in chromatin remodeling and transcriptional regulation. Although the emerging role of BRD7 in the pathophysiology of various diseases has been observed, its role in asthma remains unknown. Here, we assessed the function of BRD7 as a mediator of airway remodeling in asthma using an in vitro model. Methods: Airway smooth muscle cells (ASMCs) were challenged with tumor necrosis factor-α (TNF-α) to establish an in vitro airway remodeling model. Protein levels were examined using western blotting. Cell proliferation was measured using the cell counting kit-8 and 5-ethynyl-2′-deoxyuridine assays. Cell migration was assessed using a transwell migration assay. Results: Exposure to TNF-α dramatically decreased BRD7 levels in ASMCs. BRD7 remarkably decreased TNF-α-induced proliferation and migration of ASMCs. In contrast, ASMCs with BRD7 deficiency were more sensitive to TNF-α-induced pro-proliferative and pro-migratory effects. Mechanistically, BRD7 could repress the expression of Notch1 and block the Notch pathway in TNF-α-challenged cells. Notably, reactivation of Notch signaling substantially reversed the BRD7 overexpression-mediated effects, whereas restraining Notch signaling abolished BRD7-depletion-mediated effects on TNF-α-challenged cells. Conclusions: BRD7 inhibits the proliferation and migration of ASMCs elicited by TNF-α by downregulating the Notch pathway. This study indicates that BRD7 may exert a suppressive effect on airway remodeling during asthma.